Standardized reporting of the costs of management interventions for biodiversity conservation. Issue 5 (20th September 2018) - Iacona, Gwenllian D.; Sutherland, William J.; Mappin, Bonnie; Adams, Vanessa M.; Armsworth, Paul R.; Coleshaw, Tim; Cook, Carly; Craigie, Ian; Dicks, Lynn V.; Fitzsimons, James A.; McGowan, Jennifer; Plumptre, Andrew J.; et al.
Abstract: Effective conservation management interventions must combat threats and deliver benefits at costs that can be achieved within limited budgets. Considerable effort has focused on measuring the potential benefits of conservation interventions, but explicit quantification of the financial costs of implementation is rare. Even when costs have been quantified, haphazard and inconsistent reporting means published values are difficult to interpret. This reporting deficiency hinders progress toward a collective understanding of the financial costs of management interventions across projects and thus limits the ability to identify efficient solutions to conservation problems or attract adequate funding. We devised a standardized approach to describing financial costs reported for conservation interventions. The standards call for researchers and practitioners to describe the objective and outcome, context and methods, and scale of costed interventions, and to state which categories of costs are included and the currency and date for reported costs. These standards aim to provide enough contextual information that readers and future users can interpret the cost data appropriately. We suggest these standards be adopted by major conservation organizations, conservation science institutions, and journals so that cost reporting is comparable among studies. This would support shared learning and enhance the ability to identify and perform cost‐effective conservation. Abstract : Article impact statement : Standardized reporting of conservation costs means data in published studies can be transferable and interpretable for improved conservation.